The Physiological Response of Lettuce to Red and Blue Light Dynamics Over Different Photoperiods - Samuolienė, Giedrė; Viršilė, Akvilė; Miliauskienė, Jurga; Haimi, Perttu J.; Laužikė, Kristina; Brazaitytė, Aušra; Duchovskis, Pavelas (Frontiers in Plant Science, 2021)
This study aimed to evaluate the effect of dynamic red and blue light parameters on the physiological responses and key metabolites in lettuce, and the subsequent impact of varying light spectrums on nutritive value. We explored the metabolic changes in carotenes, xanthophylls, soluble sugars, organic acids, and antioxidants, the response of photosynthetic indices (photosynthetic (Pr) and transpiration (Tr) rates), and the intracellular to ambient CO2 concentration ratios (Ci/Ca) in lettuce (Lactuca sativa L. ‘Lobjoits Green Cos’). They were cultivated under constant (con) or parabolic (dyn) blue (B, 452 nm) and/or red (R, 662 nm) light emitting diode (LED) photosynthetic with photon flux densities (PPFDs) at 12, 16, and 20 h photoperiods, maintaining consistent daily light integrals (DLIs) for each light component in all treatments, at 2.3 and 9.2 mol m-2 per day for blue and red light, respectively. The obtained results and principle component analysis (PCA) confirmed a significant impact of light spectrum, photoperiod, and parabolic profiles of PPFD on the physiological response of lettuce. The 16 h photoperiod resulted in significantly higher content of xanthophylls (neoxanthin, violaxanthin, lutein, and zeaxanthin) in lettuce leaves under both constant and parabolic blue light treatments (BconRdyn 16h and BdynRdyn 16h, respectively). Lower PPFD levels under a 20 h photoperiod (BdynRdyn 20h) as well as higher PPFD levels under a 12 h photoperiod (BdynRdyn 12h) had a pronounced impact on leaf gas exchange indices (Pr, Tr, Ci/Ca), xanthophylls, soluble sugar contents, and antioxidant properties of lettuce leaves. The parabolic PPFD lighting profile over a 16 h photoperiod (BdynRdyn 16h) led to a significant decrease in Ci/Ca, which resulted in decreased Pr and Tr, compared to constant blue or red light treatments with the same photoperiod (BconRdyn, BdynRconat 16h). Additionally, constant blue lighting produced higher +carotene and anthocyanin (ARI) content and increased carotenoid to chlorophyll ratio (CRI) but decreased biomass accumulation and antioxidant activity.